Penolakan Pendirian Gereja Mawar Sharon di Kota Binjai Kecamatan Binjai Kota - Dicky Zuanda Atthasi, Tengku; Irwansyah, Irwansyah; Jailani, Muhammad (Jurnal el-Huda, 2024)
The rejection of the establishment of the Mawar Sharon Church in Binjai City gave rise to controversy that reflected local social, religious and political dynamics. This research aims to analyze the factors behind this rejection in Binjai Kota District. Using a descriptive qualitative approach, this research involved key informants such as FKUB administrators, church administrators, local communities, religious leaders and neighborhood heads. Data was collected through observation, interviews and documentation. The results of the research show that community rejection was triggered by four factors: the inappropriate location of what was previously a cafe, problems with permits and agreements with church administrators, concerns regarding Christianization, and the majority of the population being Muslim. Rejection was expressed through demonstrations which took place in a conducive manner. Although the local government continues to make efforts to reduce tensions, to date there has been no official decision regarding the establishment of the church.